2021
DOI: 10.7554/elife.68049
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cell aging impairs the self-organizing capacity of lung alveolar epithelial stem cells

Abstract: Multicellular organisms maintain structure and function of tissues/organs through emergent, self-organizing behavior. In this report, we demonstrate a critical role for lung mesenchymal stromal cell (L-MSC) aging in determining the capacity to form three-dimensional organoids or ‘alveolospheres’ with type 2 alveolar epithelial cells (AEC2s). In contrast to L-MSCs from aged mice, young L-MSCs support the efficient formation of alveolospheres when co-cultured with young or aged AEC2s. Aged L-MSCs demonstrated fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
(28 reference statements)
0
22
0
Order By: Relevance
“…To the best of our knowledge, we are the first to demonstrate that human lung-derived MSCs reduce human epithelial cell damage and promote alveolar epithelial regenerative responses. In a murine setting, it was shown that LMSCs promote the self-organizing capacity of alveolar epithelial progenitors in organoids, in which LMSCs of aged mice were impaired [ 25 ]. Murine BM-MSCs and their conditioned media are able to support distal lung epithelium-derived organoid formation and increase alveolar differentiation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, we are the first to demonstrate that human lung-derived MSCs reduce human epithelial cell damage and promote alveolar epithelial regenerative responses. In a murine setting, it was shown that LMSCs promote the self-organizing capacity of alveolar epithelial progenitors in organoids, in which LMSCs of aged mice were impaired [ 25 ]. Murine BM-MSCs and their conditioned media are able to support distal lung epithelium-derived organoid formation and increase alveolar differentiation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“… 76 In the organoid model of alveolospheres, aged lung MSCs have higher levels of NADPH oxidase 4(NOX4) to produce oxidants and acquire senescence-associated secretory phenotype, so that they lose the normal 3D structure with type 2 alveolar epithelial cells. 77 The senescent MSCs appeared to be less potent in tissue protection than the young ones, due to insufficient production of growth factors and chemokines. 78 Therefore, senescent MSCs deploy a more blunted secreting response to the activated immune cells compared to young MSCs, but IFNγ could partly restore the immunosuppressive deficiency of senescent ones.…”
Section: The Secretory Functions Of Mscsmentioning
confidence: 99%
“…10,54 Cellular senescence is also thought to contribute to the pathology of lung fibrosis, in which senescent cells secrete senescence-associated secretory phenotype factors to promote inflammation, tissue remodelling and cell growth. 10,56,57 NOX1 is expressed in a range of pulmonary cell types, including pulmonary epithelial cells, pulmonary vascular smooth muscle cells and bronchial epithelial cells. 58 NOX4 is expressed in macrophages, smooth muscle cells, endothelial cells, mesenchymal cells and epithelial cells.…”
Section: Roleofnox1/4inlungfibrosismentioning
confidence: 99%
“…Immune cells in turn amplify inflammatory signalling and contribute to fibrosis development by exacerbating myofibroblast differentiation and ECM deposition 10,54 . Cellular senescence is also thought to contribute to the pathology of lung fibrosis, in which senescent cells secrete senescence‐associated secretory phenotype factors to promote inflammation, tissue remodelling and cell growth 10,56,57 …”
Section: Lung Fibrosismentioning
confidence: 99%